Do Profits Drive Tax Behavior? An Empirical Analysis of CSR and Green Accounting in the Tax Avoidance Landscape - Rachman, Deviyanti Sofia; Putri, Sofie Yunida (Economics, Business, Accounting & Society Review, 2025)
Tax avoidance in the consumer goods industry poses a significant challenge for sustaining national revenue, despite this sector being a major contributor to Indonesia’s tax income. This study aims to analyze the influence of financial performance and green accounting on tax avoidance with Corporate Social Responsibility (CSR) as a mediating variable in companies in the consumer goods industry sector on the IDX in 2020-2023. A total of 30 companies in the consumer goods industry sector were obtained as samples for this study using purposive-sampling techniques. This study's methodology is quantitative research, which includes explanatory research. The variables in this study were measured using Return On Assets (ROA) toward financial performance, dummy approach toward green accounting, GRI index toward CSR, and Effective Tax Rate (ETR) toward tax avoidance. The analysis was conducted using panel data regression and the Sobel test through Interactive Mediation Tests. The study's findings indicated that financial performance has a significant impact on tax avoidance. Meanwhile, tax avoidance is not much impacted by CSR or green accounting. Green accounting and financial performance also have little bearing on CSR. Furthermore, CSR acts as an intervener between the impact of green accounting along with tax avoidance, but not between the influence of financial performance and tax avoidance. These insights contribute to a deeper understanding of the interplay between financial health, sustainability practices, and tax strategies in the consumer goods sector.